Pengaruh Motivasi, Kreativitas, Inovasi dan Modal Usaha terhadap Minat Berwirausaha - Nanda Tri Wardani; Retno Mustika Dewi (University of Merdeka Malang, 2021)
Entrepreneurial interest is believed to be the most powerful solution in solving labor problems among students. However, the phenomenon that occurs in UNESA Economic Education Study Program students is still not optimal in interpreting this solution. This study identifies the influence of motivation, creativity, innovation and venture capital on interest in entrepreneurship. The data analysis technique used multiple linear regression and descriptive statistics. A sample of 60 students used purposive sampling technique. The results of the study show that motivation, creativity and venture capital partially significant effect on entrepreneurial interest. Only innovation shows that there is no significant influence on entrepreneurial interest.